Simultaneous Determination of Six Acidic Herbicides and Metabolites in Plant Origin Matrices by QuEChERS-UPLC-MS/MS - Qiqi Jin; Qianwen Xu; Zhiyong Zhao; Wenshuai Si; Bing Bai; Lei Chen; Changyan Zhou (Molecules)
This study presents a method for the simultaneous determination of six acidic herbicides and their metabolites in various matrices, including fruits, vegetables, grains, and edible oils. The method employs acidified acetonitrile extraction combined with dispersive solid-phase extraction cleanup (dSPE) using MgSO4, Florisil, and Graphitized carbon black (GCB). The analysis was performed by ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) with electrospray ionization (ESI) in both positive and negative modes using multiple reaction monitoring (MRM). The mass concentrations of six herbicide pesticides and their metabolites were predominantly within the range of 0.0005~0.050 mg/L and exhibited strong linear relationships with the corresponding peak area, with the coefficient of determination (R2) exceeding 0.993. The limits of detection (LOD) for the method ranged from 0.0001 to 0.008 mg/kg. The recovery rates of adding recovery experiments to cabbage, chives, pear, wheat flour, and soybean oil were 69.8~120%, and the relative standard deviation (RSD) was 0.6~19.5%. The results indicate that this method is efficient and fast, and can be used for the detection of compounds in various actual matrices.